Small molecule ligand docking to genotype specific bundle structures of hepatitis C virus (HCV) p7 protein. (October 2016) - Laasch, Niklas; Kalita, Monoj Mon; Griffin, Stephen; Fischer, Wolfgang B.
Graphical abstract: Highlights: Binding poses of antivirals to hexameric bundles of p7 of HCV genotype 5a and 1b. LeadIT suggests guanidinium compounds then imino sugars, adamantanes. Rescoring with HYDE reverses the order. Favored binding sites within the pore and at outside pockets for bundle-5a. Favored binding sites at the sites of the loops for bundle-1b. Abstract: The genome of hepatitis C virus encodes for an essential 63 amino acid polytopic protein p7 of most likely two transmembrane domains (TMDs). The protein is identified to self-assemble thereby rendering lipid membranes permeable to ions. A series of small molecules such as adamantanes, imino sugars and guanidinium compounds are known to interact with p7. A set of 9 of these small molecules is docked against hexameric bundles of genotypes 5a (bundle-5a) and 1b (bundle-1b) using LeadIT. Putative sites for bundle-5a are identified within the pore and at pockets on the outside of the bundle. For bundle-1b preferred sites are found at the site of the loops. Binding energies are in favour of the guanidinium compounds. Rescoring of the identified poses with HYDE reveals a dehydration penalty for the guanidinium compounds, leaving the adamantanes and imino sugar in a better position. Binding energies calculated by HYDE and those by LeadIT indicate that all compounds are moderate binders.